Advancements in osteosarcoma management: integrating immune microenvironment insights with immunotherapeutic strategies - Liang, Hang; Cui, Min; Tu, Jingyao; Chen, Xinyi (Frontiers in Cell and Developmental Biology, 2024)
Osteosarcoma, a malignant bone tumor predominantly affecting children and adolescents, presents significant therapeutic challenges, particularly in metastatic or recurrent cases. Conventional surgical and chemotherapeutic approaches have achieved partial therapeutic efficacy; however, the prognosis for long-term survival remains bleak. Recent studies have highlighted the imperative for a comprehensive exploration of the osteosarcoma immune microenvironment, focusing on the integration of diverse immunotherapeutic strategies — including immune checkpoint inhibitors, tumor microenvironment modulators, cytokine therapies, tumor antigen-specific interventions, cancer vaccines, cellular therapies, and antibody-based treatments — that are directly pertinent to modulating this intricate microenvironment. By targeting tumor cells, modulating the tumor microenvironment, and activating host immune responses, these innovative approaches have demonstrated substantial potential in enhancing the effectiveness of osteosarcoma treatments. Although most of these novel strategies are still in research or clinical trial phases, they have already demonstrated significant potential for individuals with osteosarcoma, suggesting the possibility of developing new, more personalized and effective treatment options. This review aims to provide a comprehensive overview of the current advancements in osteosarcoma immunotherapy, emphasizing the significance of integrating various immunotherapeutic methods to optimize therapeutic outcomes. Additionally, it underscores the imperative for subsequent research to further investigate the intricate interactions between the tumor microenvironment and the immune system, aiming to devise more effective treatment strategies. The present review comprehensively addresses the landscape of osteosarcoma immunotherapy, delineating crucial scientific concerns and clinical challenges, thereby outlining potential research directions.